Pathology of Alzheimer's disease - Revesz, Tamas (Henry Stewart Talks, 2011)
Alzheimer's disease as the commonest neurodegenerative disease, Alzheimer's disease as one of the protein folding disorders, Alzheimer's disease is rarely inherited due to mutations of one of three genes, Apolipoprotein E epsilon 4 allele as genetic risk factor for Alzheimer's disease, Neuritic plaques, Neurofibrillary tangles, Amyloid-beta peptide, Tau protein